A cross-sectional study of breastfeeding device use and its determinants in mothers attending immunization outpatient department of an urban health training centre attached to a teaching medical institute - Wanjare, Amit A.; Pol, Sujata S.; Bansode-Gokhe, Seema S. (International Journal Of Community Medicine And Public Health, 2024)
Background: Breastfeeding as a practice was recommended by World Health Organization. Breastfeeding devices are used to feed the expressed breastmilk to infants, it is one determinant which is linked with both favourable and unfavourable outcomes in exclusive breastfeeding practices among term and pre-term infants. Methods: This was a cross sectional, observational study carried at an urban health training centre. The study subjects were mother and their infants residing in the urban slum. Objectives of the research were to determine the proportion of exclusive breastfeeding, to find various breastfeeding devices used by mothers and the factors associated with it. A total of 230 mother-infant dyads were included in the study. Results: Majority of mothers belonged to 21-30-year age group, housewives (93%) and Hindu by religion (68%). Majority received education till secondary school (57%) and 3.5% were illiterate. Majority had their first child before they turned 30 and most of the infants were female (55%). Over 3/4th of the infants were being exclusively breastfed, initiated on breastfeeding within first hour of birth (41%) and 1/5th received pre-lacteal feed, Breastfeeding device use was noted in 15 participants (6.5%), in which majority were using spoon followed by bottle. Mothers using breastfeeding devices showed higher proportion of exclusive breastfeeding. Conclusions: Use of breastfeeding device showed association with mother’s occupation, lower age of mother at the time of marriage and first delivery while religion and parity of mothers were not significantly associated with it.